Public expenditure on income maintenance programmes - Organisation for Economic Co-operation and Development (Paris : OECD ; [Washington, D.C. : sold by OECD Publications Center], 1976)
The report is part of a broader project on issues of resource allocation and government expenditure, launched by Working Party No.2 of the Economic Policy Committee.
Includes bibliographical references.
osc 13/6/17
Loans
Keywords: Income maintenance programs; Poor; Public expenditure